Pendampingan Kegiatan Pembelajaran Ilmu Tajwid Menggunakan Metode Praktek Langsung di Masjid Raya Mardiyah Silandit - Tini Melinda Nst; Martin Kustati; Rezki Amelia; Gusmirawati Gusmirawati (Nusantara Mengabdi Kepada Negeri, 2024)
Assistance with tajweed learning activities aims to improve children's ability to read the Qur'an in Silandit village, especially around the Mardiyah mosque, this tajweed learning assistance activity teaches children to read the Qur'an with tartil using the laws and rules of tajweed science that are good and correct, using the direct practice method can make it easier for children to understand what the teacher means because with this method the teacher can see the extent of children's development in understanding the study of tajweed by directly practicing what the teacher means. This mentoring method is carried out using the Participatory Action Research (PAR) method. The preparations that we prepared in this mentoring included preparing tajweed learning materials, followed by carrying out learning mentoring by adjusting to children's studies and focusing on the study of tajweed, then practicing direct tartil reading according to the rules of tajweed followed by children. The result of this assistance is that the assistance carried out at the Mardiyah Silandit mosque can regenerate children's enthusiasm in studying, repeating and improving the reading of the Qur'an and adding insight so that children are able to read the Qur'an tartil in accordance with the study and rules of tajweed science.